Study of Dispersion Hazard Potential of The LPG Stations Around the RDE Site in Rainy and Dry Season - Siti Alimah; June Mellawati (Jurnal Pengembangan Energi Nuklir, 2018)
STUDY OF DISPERSION HAZARD POTENTIAL OF THE LPG STATIONS AROUND THE RDE SITE IN RAINY AND DRY SEASON. There are two LPG station (SPPBE) which are the depot of filling, storage and distribution of  Liquid Petroleum Gas (LPG) namely PT. BM and PT. ISR which the distance each are 2,995 and 4,141 km from Experimental Power Reactor (RDE) site with capacity 15 and 30 tons. LPG station is a stationary source, which is one aspect of the external human induced events that need to be analyzed in the preparation of site evaluation reports to obtain site permits. Hazard potential that may occur from the depot LPG are fire, explosion and dispersion of hazardous and toxic gas. The release of LPG due to valve leakage which is then dispersed at a certain dose has potentially harmful to health, even death to the population around  the RDE site. The purpose of the study was to know the effect of seasons (rainy and dry) to the potential hazard of LPG dispersion from LPG truck tank valve to the around RDE site. The method of study are collection the atmospheric data such as wind direction and speed, temperature and humidity, collection the station LPG characteristic, such as mass of gas, diameter and length of tank, and valve diameter, etc. The atmospheric data was obtained from Pondok Betung Climatology Station, in dry, transition, and rainy seasons, furthermore data was analyzed using ALOHA software version 5.4.5. The results show dispersion from LPG release due to valve  leakage from PT. BM and PT. ISR around the RDE site, in the dry season (April), the transition (January and July) as well as the rainy season (October) does not hazardous to the RDE site. Maximum threat zone occurs in dry season at April (wind speed 1.54 m/s), which reaches radius 179 m with airborne LPG concentration 5500 ppm, radius 111 m with concentration 17000 ppm and radius 71 m with concentration 53000 ppm.